2013
DOI: 10.1016/j.jssc.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of perovskite-type SrxY1−xFeO3−δ (0.63≤x<1.0) and Sr0.75Y0.25Fe1−yMyO3−δ (M=Cr, Mn, Ni), (y=0.2, 0.33, 0.5)

Abstract: Synthesis and characterisation of perovskite SrxY1-xFeO3-d (=.63≤x<1) and Sr0.75Y0.25Fe1-yMyO3-d (M=Cr, Mn, Ni) (y= 0.2, 0.33, 0.5). Chemistry, http://dx.doi.org/10. 1016/j.jssc.2013.01.008 Access to the published version may require subscription. N.B. When citing this work, cite the original published paper. Journal of Solid State

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(20 reference statements)
5
6
0
Order By: Relevance
“…Figure demonstrates the ideal perovskite cubic cell without any additional reflections. In general, this agrees with the findings made by Biendicho et al, who observed only partial local ordering in the HREM images of Sr 0.75 Y 0.25 FeO 3−δ , due to small variations in the oxygen content that caused a formation of local structural units.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Figure demonstrates the ideal perovskite cubic cell without any additional reflections. In general, this agrees with the findings made by Biendicho et al, who observed only partial local ordering in the HREM images of Sr 0.75 Y 0.25 FeO 3−δ , due to small variations in the oxygen content that caused a formation of local structural units.…”
Section: Resultssupporting
confidence: 93%
“…Battle et al reported on Sr 2 YFe 3 O 8+ y prepared at 1573 K in air by a standard solid‐state method . The samples of the general composition Sr x Y 1− x FeO 3−δ with x = 0, 0.25, 0.5, 0.75, 1 and 0.63 ≤ x < 1 were synthesized in air at 1473 and 1573 K, respectively. The synthesis was performed inside silica tubes sealed under vacuum (10 −2 mbar) with subsequent firing at 1100–1150°C; this allowed to prepare the ordered phase Sr 3 YCo 4 O 10.5+δ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher temperatures, the conductivity starts to decrease due to oxygen loss and associated decrease of charge carrier concentration due to a reduction of the average oxidation state of the B-cations. This is similar to what reported in related systems-Sr 3 FeNiO 7−δ [10], Sr 3 Fe 2 O 7−δ [10], and Sr x Y 1−x FeO 3−δ [28] and Sr 3−x Y x Fe 1.25 Ni 0.75 O 7−δ [14]. It should also be noted that conductivity for the Pr-containing sample is an order-of-magnitude higher than that reported for the Y-system.…”
Section: Discussionsupporting
confidence: 91%
“…25 Ni 0.75 O 7 À δ [19]. The substitution of Sr by Y in Sr 3 (Ni,Fe) 2 O 7 À δ RP phases could possibly decrease the thermal expansion due to the higher strength of the Y-O bond as compared to the Sr-O bond [20].…”
Section: Introductionmentioning
confidence: 99%